Nilai Pembelajaran dalam Motif Batik - Sudardi, Bani (Hiski Malang, 2021)
Batik motif is a form of design included in the study of fine arts. Batik motifs are inspired from various things around us, such as natural events, family and social events, and literary works, either written or oral literary works. Javanese batik is closely related to the stories of the chronicle of the royal family. Batik motifs are closely related to the literary works that exist in the society as the owner of the motive. In Jambi, for example, batik motifs sanggat ship is a very famous. This motif was inspired by the existence of a ship that failed (sanggat). The educational values inspired from this motif is that in life one must be careful in determining the direction of life in order not to run aground. Chinese Lasem community has a motif called the Hong bird motif. The appearance of the motive was inspired by the myth of the Hong bird in the Chinese tradition which is a lucky bird. The Hong Bird is the king of bird and its element of fire is strongest among all beings. This bird is a symbol of immortality because of its ability to live after death. There are four animals in important Chinese mythology: dragons, turtles, kilns, and Hong birds. Among them Hong bird and dragon are frequently appear in batik motifs. The education value of these Chinese motif is the God blessing in the creatures. The study shows that artworks, literature and batik motifs, are interrelated each other. The education values emerged from this batik motif is valuable for people’s life.